Individualized Bone‐Protective Management in Long‐Term Cancer Survivors With Bone Metastases. (24th June 2021) - Rachner, Tilman D; Coleman, Robert; Hadji, Peyman; Hofbauer, Lorenz C
ABSTRACT: Antiresorptive therapy is an important component of a multimodal approach to treating patients with advanced malignancies and metastatic bone disease. Over the past decade, overall survival of affected patients has improved in most cancer entities, and long‐term disease control is a realistic goal in many cases. There are emerging clinical studies showing the benefits of an initial antiresorptive therapy using bisphosphonates or denosumab. However, some adverse events of these therapies, such as osteonecrosis of the jaw, correlate with the cumulative doses given, and there is an increasing clinical need for new antiresorptive concepts to treat long‐term survivors. This review summarizes the clinical evidence of antiresorptive therapies across different cancers with bone involvement and presents concepts of dose‐reduction protocols for long‐term survivors with established metastatic bone disease. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).